2019
DOI: 10.1161/strokeaha.119.025723
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the Inferior Cerebellar Peduncle After Middle Cerebral Artery Stroke

Abstract: Background and Purpose— Deafferentation of the cortico-ponto-cerebellar pathway has been proposed as a key mechanism of crossed cerebellar diaschisis. Although the cerebellum receives afferent stimuli from both cortico-ponto-cerebellar and spinocerebellar pathways, evidence on whether spinocerebellar deafferentation contributes to a hypofunctional cerebellum is lacking. Therefore, we aimed to determine whether changes in the spinocerebellar pathway occur after middle cerebral artery stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Our nding of decreased FA and increased MD in the contralesional ICP seems inconsistent with the structural changes in this area in subacute supratentorial stroke patients. Kim et al [6] found a marked FA reduction and MD increase in the contralesional ICP at 27 days after stroke in the patient group compared with the control group. This discrepancy in results may be due to experimental design differences.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our nding of decreased FA and increased MD in the contralesional ICP seems inconsistent with the structural changes in this area in subacute supratentorial stroke patients. Kim et al [6] found a marked FA reduction and MD increase in the contralesional ICP at 27 days after stroke in the patient group compared with the control group. This discrepancy in results may be due to experimental design differences.…”
Section: Discussionmentioning
confidence: 93%
“…Based on the ndings of previous studies, our result that lower limb motor function was also associated with ICP integrity is noteworthy. Kim et al [6] considered that insu cient peripheral proprioceptive stimulation to the cerebellum from a weak lower limb may result in secondary degeneration in the contralesional spinocerebellar pathway, but they could not fully determine whether FA reduction in the contralesional ICP was affected by hemiplegic muscles, a hypofunctional cerebellum, or both due to the retrospective and cross-sectional design of their study. We found that ALFF in the contralesional anterior lobe of the cerebellum reduced sharply at week 4 but increased somewhat at week 12 after onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For two decades, various methods have been used to study the impact of CCD on stroke-related symptoms like postural asymmetry [1]. It is generally believed that CCD is caused by an interruption of either the cortico-ponto-cerebellar pathway or the dentate-rubro-thalamo-cortical pathway [11,12]. However, no study has been done to explore the close relationship between GHS and CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al [ 6 ] found a secondary degeneration characterized by reduced fractional anisotropy (FA) and elevated mean diffusivity (MD) in the contralesional ICP in 23 patients with subacute middle cerebral artery (MCA) stroke, a change associated with patients’ ambulatory and lower limb (LL) function. They believed that insufficient peripheral proprioceptive stimulation to the cerebellum due to LL weakness might result in secondary changes in the spinocerebellar pathway, but they could not fully determine whether FA reduction in the contralesional ICP was affected by hemiplegic muscles, a hypofunctional cerebellum, or both, due to the retrospective and cross-sectional design of their study.…”
Section: Introductionmentioning
confidence: 99%